Dampak Negatif Media Sosial Bagi Remaja Berdasarkan Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Sanusi, Sanusi; Sardo Afrizal Hasugian; Sella Triamami; Sofwan, Edi; Taufik Kurrohman (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Defamation is one of the criminal acts that fall into the qualification of insult. Defamation is regulated in Article 310 of the Criminal Code and in Article 27 Paragraph (3) of the Electronic Information and Transaction Law. The purpose of the existence of this legal rule on defamation is to protect the dignity and dignity of every person, especially regarding the honorable self-esteem (eer) and good name (goeden naam) of a person due to the use of social media that has a negative impact. The formulation of the problem discussed in this paper is to analyze (1) The regulation of the crime of defamation in the Criminal Code and Article 27 Paragraph (3) of the Law on Information and Electronic Transactions due to the use of social media that has a negative impact. The writing method used is normative research, which is research that relies on secondary data sources as the main reference data. The results obtained from the research were concluded (1) Regulations regarding the crime of defamation are regulated in Article 27 paragraph (3) of the Law on Information and Electronic Transactions. To determine whether the defamation element in the ITE Law has been fulfilled, it must refer to Article 310 of the Criminal Code. The negative impact caused is that the use of social media itself makes adolescents lazy and rarely socializes face-to-face with others so that it has the potential to make adolescents become anti-social individuals, addiction which leads to reduced time efficiency, consumption, mental health of adolescents, affects the decline of moral values and ethics of the younger generation, decreases the quality of critical thinking of adolescents, and the ease of being influenced by information that is not yet known to be true as seen from the ITE Law issued by the government to be a guideline in the implementation of Article 27 paragraph (3) of the ITE Law which aims to create legal certainty with solutions such as setting a healthy time limit; Build awareness of the emotional impact; Develop critical skills; Provide an understanding of online privacy; Focus on offline social interactions; Implementation of the ITE Law.